Changes in Immunoreactivity of Sensory Substances within the Enteric Nervous System of the Porcine Stomach during Experimentally Induced Diabetes - Michał Bulc; Katarzyna Palus; Jarosław Całka; Łukasz Zielonka (Journal of Diabetes Research)
One of the most frequently reported disorders associated with diabetes is gastrointestinal (GI) disturbance. Although pathogenesis of these complications is multifactorial, the complicity of the enteric nervous system (ENS) in this respect has significant importance. Therefore, this paper analysed changes in substance P- (SP-), calcitonin gene-related peptide- (CGRP-), and leu5-enkephalin- (L-ENK-) like immunoreactivity (LI) in enteric stomach neurons caused by chemically induced diabetes in a porcine model. Using double immunofluorescent labelling, it was found that acute hyperglycaemia led to significant changes in the chemical coding of stomach enteric neurons. Generally, the response to artificially inducted diabetes depended on the “kind” of enteric plexus as well as the stomach region studied. A clear increase in the percentage of neurons immunoreactive to SP and CGRP was visible in the myenteric plexus (MP) in the antrum, corpus, and pylorus as well as in the submucosal plexus (SmP) in the corpus. For L-ENK, an increase in the number of L-ENK-LI neurons was observed in the MP of the antrum and SmP in the corpus, while in the MP of the corpus and pylorus, a decrease in the percentage of L-ENK-LI neurons was noted.